Guest Editorial - Singh, A.P. (DESIDOC Journal of Library & Information Technology, 2016)
Libraries are one of the oldest human institutions. Librarianship too has been in practice for a long time and across cultures, this practice being an expression of the social practices of these cultures. The development of librarianship was closely associated with the recording of messages and information on manuscripts or papers and consequently with the collection of records in individual or public interest. Majority of the activities associated with contemporary librarianship were a part of day-to-day work culture. Later on however, with the popularisation of information sources and the rapid growth of their collection, librarianship came to be recognised as an independent profession. Subsequently, the need for professional training was identified for providing best support to its user community. And over time, specialised issues and settings have translated into academic programmes of professional schools in the higher education system.